Pengaruh Kekerasan Verbal Orangtua terhadap Konsep Diri Remaja - Hamiyati; Awal, Rahmatia Narita; Nugraheni, Prastiti Laras (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2022)
This study aims to analyze the effect of parental verbal abuse on adolescents self-concept. The approach used in this study is quantitative associative with a survey method using questionnaire to collect the data. The population in this study was high school students of SMA Negeri 1 Leuwiliang Kabupaten Bogor, with a total sample of 103 respondents selected with the purposive sampling technique. This study uses tests of normality, linearity, and hypotheses as a pre-requisite test. Based on data result, it is known that majority sample are categorized as low level of parental verbal abuse (69,9%) and the adolescents self concept received by the majority sample are belong to middle category (53,4%). Data calculation which used IBM SPSS Statistics 25 shows that parental verbal abuse has a negative and significant effect on adolescents self concept (P-Value = 0.000 < 0.050. This study shows that the higher parental verbal abuse level, the lower adolescents self-concept, . The coefficient of determination obtained is 27,4%, which means that parental verbal abuse affect on adolescents self-concept by 27,4% and the other 72,6% is influenced by other factors not examined in this study.